Effect of KCl and Na2SO4 on the solubility of glycine and DL-alanine in water at 298.15 K - Ferreira, Luísa (2010)
The solubility of glycine and DL-alanine in aqueous systems of KCl and Na2SO4 at 298.15 K was measured at different salt concentrations using the analytical gravimetric method. The experimental data obtained in this work and those previously reported in the literature for the same systems were compared, and it was possible to show a big discrepancy for the water- KCl-amino acid systems and a very satisfactory agreement for the water-Na2SO4-amino acid systems. The solubility data from this work and the activity coefficients data from literature were used to explore the potentialities of the Pitzer-Simonson-Clegg equations for the thermodynamic description of the ternary systems water-KCl with glycine or DL-alanine at 298.15 K. This model, with five adjustable parameters, gives a global root-mean-square deviation of 0.0036 for the correlation of the activity coefficients and 0.63 g/(kg of water) for the solubility in those ternary systems.